RESPONDER - diagnosis of pathological complete response by vacuum-assisted biopsy after neoadjuvant chemotherapy in breast cancer: a multicenter, confirmative, one-armed, intra-individually-controlled, open, diagnostic trial - Heil, Jörg; Sinn, Peter; Richter, Hannah; Pfob, André; Schäfgen, Benedikt; Hennigs, André; Riedel, Fabian; Thomas, Bettina C.; Rauch, Geraldine; Golatta, Michael (BMC cancer, 2018)
Neoadjuvant chemotherapy (NACT) is a standard approach of the multidisciplinary treatment of breast cancer. Depending on the biological subtype a pathological complete response in the breast (bpCR) can be achieved in up to 60% of the patients. However, only limited accuracy can be reached when using imaging for prediction of bpCR prior to surgery. Due to this diagnostic uncertainty, surgery after NACT is considered to be obligatory for all patients in order to either completely remove residual disease or to diagnose a bpCR histologically. The purpose of this trial is to evaluate the accuracy of a vacuum-assisted biopsy (VAB) to diagnose a bpCR after NACT prior to surgery.
Gesehen am 25.09.2018